Leadership Management of the Head of Madrasah Diniyah Takmiliyah Awaliyah to Improve Teachers' Work Ethic - Ahyani; Siswanto, Romi; Romadhan, Syahru (Journal of Education and Learning Innovation, 2024)
This study used a qualitative approach with a case study type by taking a single case. Data collection in this study used participant observation techniques, in-depth interviews, and documentation. The research informants were Madrasah administrators, namely the Head of Madrasah Diniyah Takmiliyah Awaliyah Miftahul Mutaalimin, teachers, and students. The data that has been collected is checked for its validity using a triangulation strategy. Technical analysis of data is done by collecting data, reducing data, displaying data, and drawing conclusions. The results of this thesis research are as follows: (1) Madrasah Principal Leadership Management (Umi Minasih) Shaping Madrasah Education Quality is democratic and charismatic, (2) Madrasah Principal Leadership Strategy in Shaping Madrasah Education Quality by: a). Increasing the teacher's work ethic, b). Improving Student Quality, (3) Implications of the Madrasah Principal's Leadership in Shaping the Quality of Madrasah Education by: a). Communicating with Teachers, b). Creating a comfortable and full of togetherness atmosphere and improving the teacher's work ethic.